Mechanical Behavior Under Cyclic Loading of the 18R-6R High-hysteresis Martensitic Transformation in Cu-Zn-Al alloys with Nanoprecipitates - de Castro Bubani, Franco (2013)
Mechanical damping applications could benefit from the large hysteresis, large pseudoelastic strain and the fact that the transformation stresses of the 18R↔6R martensite–martensite transformation depend very little on temperature in Cu-based alloys. This work presents the 18R↔6R mechanical cycling behavior of CuZnAl shape-memory alloy single crystals with electronic concentration e/a¼1.48. A fine distribution of gamma phase nanoprecipitates is introduced to prevent plastic deformation of the 6R phase. Results show that, although significant 6R stabilization is observed at very low frequencies (below 10−2 Hz), it is possible to obtain more than 1000 stable pseudoelastic cycles with only minor changes in transformation stresses and hysteresis width at frequencies above 10−1 Hz. A more pronounced decrease in transformation stresses is observed after 1000 cycles. Nevertheless, the decrease in hysteresis is small up to 2000 cycles. Reported and present results indicate that pair interchange of atoms can explain the stabilization of 6R under quasistatic experimental conditions. However, at higher frequencies of cycling, stabilization of this martensite shows additional features, leading to a dynamic stabilization with slight effects on the mechanical behavior at the required frequency and number of cycles. On the whole, the behavior of this transformation is unique and very promising.